2014
DOI: 10.1097/gme.0000000000000257
|View full text |Cite
|
Sign up to set email alerts
|

Use of pragmatic community-based interventions to enhance recruitment and adherence in a randomized trial of Tai Chi for women with osteopenia

Abstract: Objectives To qualitatively evaluate the feasibility of utilizing a pragmatic network of community-based Tai Chi schools to deliver 9-month exercise interventions to osteopenic women and to explore the impact of this design feature on facilitators and barriers to trial recruitment and participant adherence during and following the trial. Methods Within a randomized trial comparing 9 months of Tai Chi plus usual care to usual care alone for post-menopausal women with moderately low bone mass, exit interviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 57 publications
0
34
0
Order By: Relevance
“…Each of these elements are paramount in a class of tai chi where all participants are part of a unique shared transformative experience, and the environment fosters connection, support and shared success. Recent qualitative studies linked to clinical trials of tai chi support the relevance of each of these first three facilitators of self-efficacy (15, 27,28). The fourth precept refers to physiological cues that can feed back on self-efficacy, and this can be positive or negative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of these elements are paramount in a class of tai chi where all participants are part of a unique shared transformative experience, and the environment fosters connection, support and shared success. Recent qualitative studies linked to clinical trials of tai chi support the relevance of each of these first three facilitators of self-efficacy (15, 27,28). The fourth precept refers to physiological cues that can feed back on self-efficacy, and this can be positive or negative.…”
Section: Discussionmentioning
confidence: 99%
“…Tai chi incorporates cultivation of mindfulness, slow deep breathing, and low-impact physical exercise. Importantly, it has been described as modifiable, non-threatening, accessible to the elderly and deconditioned, and prior studies have suggested increases in self-efficacy (12, 13, 14, 15). We have previously reported that a 12 week tai chi program in patients with HF was effective in increasing exercise self-efficacy, as well as disease-specific quality of life and mood, as compared to an education control.…”
Section: Introductionmentioning
confidence: 99%
“…All TC interventions were administered pragmatically at 1 of 5 prescreened TC schools within the Boston area that met specific guidelines described elsewhere. 23 , 24 In brief, schools were chosen to ensure that they provided valid, stable TC programs led by experienced teachers. Eligibility criteria included long-standing community-based programs, curricula taught in English language that emphasized core TC principles, and curricula based on Yang, Wu, Chen, or Sun TC styles.…”
Section: Methodsmentioning
confidence: 99%
“…Few research studies have researched the feasible differences between these modes; however, just as peer support is important for interventions and rehabilitation [115][116][117], so it is for Qigong [110]. Therefore, this gap provides scholars with opportunities for health promotion.…”
Section: Discussion and Future Research Directionsmentioning
confidence: 99%